PENGARUH SIKAP, NORMA SUBJEKTIF, DAN KONTROL PERILAKU TERHADAP INTENSI KEWIRAUSAHAAN MAHASISWA PTS DI PALEMBANG - Yun Suprani (JURNAL KOMPETITIF, 2015)
ABSTRACT Entrepreneurship development has become a national issue, because it is believed entrepreneurship is the key to a number of desirable social outcomes, including reducing unemployment. One of the causes of high unemployment I Indonesia due to lack of entrepreneurial intentions, especially among students of fact in order to stimulate the economy is strong, it takes at least 2% of the population who have an entrepreneurial spirit. The reality in Indonesia there are about 1% of the population are self-employed.This study will be made by using the Theory of Planned Behaviour approach (TPB). This behavior theory is closely related to aspects of entrepreneurship motivation. This means that entrepreneurship can be learned and mastered. Entrepreneurship can be a job and a career choice for college graduates, if the student's self there is no intention and motivation to become a entrepreuneur. This study will be conducted over six months in Palembang, from April 2014 through October 2014 and will examine the factors that influence entrepreneurial intentions Palembang students that attitude, subjective norm and selfcontrol. From the research that has been conducted on a sample of 100 students PTS Palembang, can be of value in the following regression: Y = 11.435 + 0.271 + 0.227 X1 X2 X3 + 0.215 + e Constant of 11.435 states that if there is no increase in the variable Attitudes, Subjective Norms and Behavior Control then Intention Entrepreneurship remains at 11.435 a balanced unit, while the view that the regression coefficient of 0.271 attitude variables, Subjective Norms of Behavior Control of 0.227 and 0.215 means that the tendency the projected changes between variables Attitudes, Subjective Norms and Behavior Control for Entrepreneurship intensity variable indicates that any change or improvement of variables Attitudes, Subjective Norms and Behavior Control at 100% then also lead to an increase in the variable intensity of Entrepreneurship at 27.1%, 22.7% and 21.5%. While the magnitude of correlation (R) variable Attitudes, Subjective Norms and Behavior Control for Enterprise intensity of 0.621 means that showed a very strong correlation and positive (unidirectional) amounted to 62.1%, while the rest is influenced by other variables that are not diteliti.sebesar 37, 9%. Key Words: subjective norm, behavior control, intention entrepreneurship